American Ways : - Datesman, Maryanne Kearny (Pearson Education ESL., 2014)
As the cultural diversity of the United States continues to increase, the issues surrounding multiculturalism continue to be of great importance. With updates throughout and a fresh, new design, the Fourth Edition of American Ways retains its values-based perspective in examining what makes the U.S. unique -- and how traditional values influence various aspects of American life such as religion, business, government, race relations, education, recreation, and family.